PENGARUH PERMAINAN BOLA CERIA TERHADAP PERILAKU KERJASAMA ANAK DI TAMAN KANAK KANAK JABAL RAHMAH PADANG - Nurhafizah, Nurhafizah; Chaniago, Rahma Defy (Universitas Islam Malang, 2019)
This article is written based on the results of research conducted based on the facts that occur in kindergarten Jabal Rahmah Padang, that the cooperative behavior of children has not yet developed due to lact of activities to train cooperative behavior in children. Learning activities in schools are carried out individually by the child, so that it affects the cooperative behavior of children. This study aims to determine the effect of cheerful ball play on the cooperative behavior of children. This research method uses a quantitative approach with a quasi-experimental design. Data collection techniques used are tests, and processed by the difference test (t-test). After the data is processed, it is seen that the children in the experimental class with a cheerful ball game have a higher average value than the control class with a block game. So it can be concluded that the cheerful ball game affects the cooperative behavior of children in kindergarten Jabal Rahmah Padang.